2016
DOI: 10.1134/s0036024416030158
|View full text |Cite
|
Sign up to set email alerts
|

On the applicability of Young–Laplace equation for nanoscale liquid drops

Abstract: Abstract-Debates continue on the applicability of the Young-Laplace equation for droplets, vapor bubbles and gas bubbles in nanoscale. It is more meaningful to find the error range of the Young-Laplace equation in nanoscale instead of making the judgement of its applicability. To do this, for seven liquid argon drops (containing 800, 1000, 1200, 1400, 1600, 1800, or 2000 particles, respectively) at T = 78 K we determined the radius of surface of tension and the corresponding surface tension by molecular dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…While modeling on the basis of classical density functional theory has predicted negative values of δ for liquid Lennard-Jones (LJ) droplets [13,14], simulations of droplets have estimated both negative and positive values of δ. For example, Yan, et al [15] performed MD simulations of liquid argon nanodroplets with sizes ranging from 800 to 2000 atoms at 78 K, as modelled using the LJ potential. They evaluated the pressure tensor, and using the Young-Laplace equation they concluded that δ is positive for LJ nanodroplets.…”
Section: Introductionmentioning
confidence: 99%
“…While modeling on the basis of classical density functional theory has predicted negative values of δ for liquid Lennard-Jones (LJ) droplets [13,14], simulations of droplets have estimated both negative and positive values of δ. For example, Yan, et al [15] performed MD simulations of liquid argon nanodroplets with sizes ranging from 800 to 2000 atoms at 78 K, as modelled using the LJ potential. They evaluated the pressure tensor, and using the Young-Laplace equation they concluded that δ is positive for LJ nanodroplets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we can conclude that even at the sub-10 nm scale, the Young−Laplace equation is still applicable within some small tolerance, which is consistent with the findings of some previous studies. 59,60 However, when the surface tension value γ* is estimated by applying the Young−Laplace equation to each individual data point, then a trend emerges where γ* increases nearly linearly with decreasing inverse bubble radius for both the mW and TIP4P/2005 models (see Figure 7). Thus, formation of the convex liquid−vapor surface results in a smaller free energy penalty than for the planar surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, the applicability of the Young-Laplace equation on the nanoscale remains a subject of debate. [32][33][34][35][36][37][38]…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we have not come across any reports of this approach in the literature, nor has it been theoretically demonstrated by others. Moreover, the applicability of the Young–Laplace equation on the nanoscale remains a subject of debate 32–38 …”
Section: Introductionmentioning
confidence: 99%